2020
DOI: 10.1002/cphc.202000039
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Solvation Model with First Solvation Shell for Calculation of Solvation Free Energy

Abstract: We present a hybrid solvation model with first solvation shell to calculate solvation free energies. This hybrid model combines the quantum mechanics and molecular mechanics methods with the analytical expression based on the Born solvation model to calculate solvation free energies. Based on calculated free energies of solvation and reaction profiles in gas phase, we set up a unified scheme to predict reaction profiles in solution.The predicted solvation free energies and reaction barriers are compared with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…The free energy of solvation, also computed using the Gaussian16 package with the CCSD­(T)/aug-cc-pVTZ level of theory and the SMD model, of the transition state (F···CH 3 CH 2 ···Cl) − is −76.9 kcal/mol; for the two neutral molecules, CH 3 CH 2 Cl and FCH 2 CH 3 , they are −1.05 and −1.14 kcal/mol, respectively. The free energies of solvation of the two anions of F – and Cl – taken from previous experimental studies , are −103.2 and −77.0 kcal/mol, respectively. According to these numbers shown in Figure , as well as the reaction path in terms of free energy in the gas phase (the upper panel), the free energy barrier height can be predicted at 16.2 kcal/mol, and the free energy of reaction at −8.3 kcal/mol, having an excellent agreement with our computed ones, 16.8 and −9.7 kcal/mol at the CCSD­(T)/MM level of theory.…”
Section: Resultsmentioning
confidence: 99%
“…The free energy of solvation, also computed using the Gaussian16 package with the CCSD­(T)/aug-cc-pVTZ level of theory and the SMD model, of the transition state (F···CH 3 CH 2 ···Cl) − is −76.9 kcal/mol; for the two neutral molecules, CH 3 CH 2 Cl and FCH 2 CH 3 , they are −1.05 and −1.14 kcal/mol, respectively. The free energies of solvation of the two anions of F – and Cl – taken from previous experimental studies , are −103.2 and −77.0 kcal/mol, respectively. According to these numbers shown in Figure , as well as the reaction path in terms of free energy in the gas phase (the upper panel), the free energy barrier height can be predicted at 16.2 kcal/mol, and the free energy of reaction at −8.3 kcal/mol, having an excellent agreement with our computed ones, 16.8 and −9.7 kcal/mol at the CCSD­(T)/MM level of theory.…”
Section: Resultsmentioning
confidence: 99%
“…81 The adequate number has to be a close approximation of at least the first solvation shell. 83,84 This is again not enough, as the solvation shell is not static, so one needs to consider multiple arrangements. 26 The broad distributions of energy values observed demonstrated that minute changes in positions of few solvent molecules were enough to give significant spreads in the single point energies.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Our data and the preceding discussion underscore why placing a large number of solvent molecules by hand is not a viable solution. It is easy to get inconsistent behavior, as well as lack of limiting value in energy for a series of hand-picked solvent configurations. , It can be argued that no such limiting value exists because the actual answer is a broad distribution, where only an average or certain central tendency makes sense. It is not possible to “guess” the average without approximating over the solvent dynamics to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative, an intermediate model can be used, linking a small number of explicit solvent molecules interacting with the solute and a continuous model describing the rest of the system. This model, known as hybrid discrete-continuum, 19 is useful for studying solvent effects on reaction mechanisms and energies [20][21][22][23] as well as on electronic and vibrational spectra. [24][25][26][27][28][29] It has also been shown to be relevant for ion solvation.…”
Section: Introductionmentioning
confidence: 99%